The safety of tenofovir-emtricitabine for HIV pre-exposure prophylaxis (PrEP) in individuals with active hepatitis B - Marc M. Solomon (2018)
Copyright © 2015 Wolters Kluwer Health, Inc. All rights reserved. Background: Pre-exposure prophylaxis (PrEP) with daily oral emtricitabine and tenofovir disoproxil fumarate (FTC/TDF) prevents HIV infection. The safety and feasibility of HIV PrEP in the setting of hepatitis B virus (HBV) infection were evaluated. Methods: The Iniciativa Profilaxis Pre-Exposición study randomized 2499 HIV-negative men and transgender women who have sex with men to once-daily oral FTC/TDF versus placebo. Hepatitis serologies and transaminases were obtained at screening and at the time PrEP was discontinued. HBV DNA was assessed by polymerase chain reaction, and drug resistance was assessed by population sequencing. Vaccination was offered to individuals susceptible to HBV infection. Results: Of the 2499 participants, 12 (0.5%; including 6 randomized to FTC/TDF) had chronic HBV infection. After stopping FTC/ TDF, 5 of the 6 participants in the active arm had liver function tests performed at follow-up. Liver function tests remained within normal limits at post-stop visits except for a grade 1 elevation in 1 participant at post-stop week 12 (alanine aminotransferase = 90, aspartate aminotransferase = 61). There was no evidence of hepatic flares. Polymerase chain reaction of stored samples showed that 2 participants in the active arm had evidence of acute HBV infection at enrollment. Both had evidence of grade 4 transaminase elevations with subsequent resolution. Overall, there was no evidence of TDF or FTC resistance among tested genotypes. Of 1633 eligible for vaccination, 1587 (97.2%) received at least 1 vaccine; 1383 (84.7%) completed the series. Conclusions: PrEP can be safely provided to individuals with HBV infection if there is no evidence of cirrhosis or substantial transaminase elevation. HBV vaccination rates at screening were low globally, despite recommendations for its use, yet uptake and efficacy were high when offered.